ANALISIS KESIAPAN SISWA DALAM MENGHADAPI PEMBELAJARAN KODING DAN KECERDASAN ARTIFISIAL SISWA SMA DAN SMK KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Rosma Kumala Dewi; Rahmad Al Rian; Edi Ismanto (STKIP Subang, 2026)
The development of the Industrial Era 4.0 and Society 5.0 has brought significant changes to the field of education, especially in the use of technology in the learning process. This condition requires students to be prepared to face technology-based learning such as coding and artificial intelligence. This study aims to determine the level of readiness of senior high school and vocational high school students in facing coding and artificial intelligence learning in Pangkalan Kuras District, Pelalawan Regency. The research employed a quantitative descriptive method with an evaluative approach. The research subjects consisted of tenth-grade students from SMAN 1 Pangkalan Kuras, SMAN 2 Pangkalan Kuras, SMKN 1 Pangkalan Kuras, and SMK Amanatulhuda Surya Indah. Data collection was conducted using questionnaires with the Proportional Random Sampling technique and a Likert scale, then analyzed using descriptive statistics in the form of percentages. Proportional Random Sampling is a sampling technique carried out randomly according to the proportion of students in each school, and the sample size was determined using the Slovin formula. The results showed several indicators of student readiness in facing coding and artificial intelligence learning among senior high school and vocational high school students in Pangkalan Kuras District, Pelalawan Regency. Overall, students’ readiness was categorized as very ready, with a percentage level of 83.6%. Meanwhile, the dominant aspect of students’ readiness in facing coding and artificial intelligence learning was the skills aspect.